Characteristics of Industrial Learning in Japanese Elementary School Social Studiesï¼šIn the case of the fifth grade "Showdown, Which Manufacturing Show!" - Shirai, Katsuhisa (The Indonesian Journal of Social Studies, 2019)
The purpose of this research is to clarify the characteristics of industrial learning in Japanese elementary school social studies and to compare viewpoints on social studies in Indonesia. The following three points have become clear as a result of this research, as part of industrial learning in elementary school social studies in Japan, at the class practice level. First, in industrial learning in elementary school social studies in Japan, a unit design was conducted using factories in the area as teaching materials. Second, lessons were conducted through factory tours from the perspective of increasing awareness of the efforts of those working in factories. Third, learning processes involving learners were developed, such as research, visit activities, and discussions centered on children?s problem awareness. The above three points are considered in order to make suggestions for the improvement of industrial learning in the social studies of elementary schools in Indonesia.